2021
DOI: 10.3892/ol.2021.13003
|View full text |Cite
|
Sign up to set email alerts
|

Gold nanoparticles enhance microRNA 31 detection in colon cancer cells after inhibition with chlorogenic acid

Abstract: In the present study, the inhibitory effect of chlorogenic acid (CGA), a phenolic compound with potential antitumor effects, on circulating microRNA 31 (miR-31), was evaluated in RKO colon cancer cells. The capacity of gold nanoparticles (AuNPs) to enhance miR-31 quantification after treatment with CGA was assessed. RKO cells were treated with different concentrations of CGA for 24, 48 and 72 h, after which AuNPs coupled to CD81 were added to the supernatants. Total RNA was extracted, and miR-31 was quantified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…Indeed, a salicylic acid derivative, anacardic acid, acts as a histone deacetylase inhibitor in human cancer cells [ 26 ]. Another explanation could come from research on polyphenols where one of the major hydroxycinnamic acids in lettuce, chlorogenic acid, was identified as histone acetyltransferase inhibitor [ 27 ], and was shown to inhibit proliferation of colon cancer cells [ 18 ] and ameliorate other diseases [ 19 ] through micro-RNA-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, a salicylic acid derivative, anacardic acid, acts as a histone deacetylase inhibitor in human cancer cells [ 26 ]. Another explanation could come from research on polyphenols where one of the major hydroxycinnamic acids in lettuce, chlorogenic acid, was identified as histone acetyltransferase inhibitor [ 27 ], and was shown to inhibit proliferation of colon cancer cells [ 18 ] and ameliorate other diseases [ 19 ] through micro-RNA-dependent mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…It is believed that altered patterns of DNA methylation play a role in the progression of cancer and pathogenesis of other disease [ 16 ]. Interestingly, polyphenols from lettuce, iodine, and salicylic acid were all reported to exert certain epigenetic effects [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…CGA and its metabolites can increase the levels of pro-caspase-3 and activated caspase-3 in human colon cancer cell lines such as Caco-2 [280]. CGA combined with lactoferrin arrests SW480 cells at the G 0 /G 1 phase and decreases cell viability [281].…”
Section: Colorectal Cancermentioning
confidence: 99%
“…Thus, coffee suppressed the KRAS signaling pathways including the mitogen-activated protein kinase (MAPK) and phosphatidylinositol 3-kinase (PI3K) signaling pathways and further exerted an inhibitory effect on cell proliferation [ 30 ]. In 2021, Luque-Badillo et al found in vitro that one of the coffee active ingredients, CGA, could decrease colon cancer cell proliferation by inhibiting the expression of the miR-31 oncogene which played a vital role in promoting cell-cycle progression [ 31 ].…”
Section: The Impact Of Coffee During Pregnancy and In Diseasesmentioning
confidence: 99%